REGULATING THE REVENUES OF LOCAL BUDGETS THROUGH INTER-BUDGETARY RELATIONS (World Bulletin of Management and Law, 2025)
The article describes the procedure for the formation of local budget revenues and the scientific and practical basis of inter-budgetary relations in strengthening local budget revenues. Regulation of local budget revenues is based on the functioning mechanism of inter-budgetary relations, as well as transfers allocated to local budgets, ways of strengthening local budget revenues through them. Based on the conducted research, scientific proposals and conclusions were formed.